2018
DOI: 10.1007/s11695-018-3285-x
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment of Obesity in Young People—a Systematic Review and Meta-analysis

Abstract: Obesity in the young is increasingly prevalent. Early, effective intervention is paramount. Treatment options are lifestyle modifications, pharmacological therapies, endoscopic treatments and bariatric surgery. However, the relative effectiveness of these treatments in young patients remains unclear. We systematically identify and meta-analyse studies evaluating weight loss treatments in young people (< 21 years) with obesity. From 16,372 identified studies, 83 were eligible for meta-analysis. Bariatric surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 60 publications
0
7
0
2
Order By: Relevance
“…The study concludes that, as opposed to nonsurgical obesity therapies, bariatric surgery results in a larger decrease in BMI in the short and long term. 43 As a result of these findings, doctors and patients should recommend bariatric surgery at a lower threshold where lifestyle and pharmacological treatments have failed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concludes that, as opposed to nonsurgical obesity therapies, bariatric surgery results in a larger decrease in BMI in the short and long term. 43 As a result of these findings, doctors and patients should recommend bariatric surgery at a lower threshold where lifestyle and pharmacological treatments have failed.…”
Section: Discussionmentioning
confidence: 99%
“…44 This is supported by the study of Selvendran et al that also concluded that overall lifestyle and pharmacological treatments have similar effects on BMI reduction, and that metformin has similar effects on BMI reduction independent of the time period over which it is prescribed. 43 Another review showed that metformin has little discernible weight-loss effect following longterm use. 45 Regarding surgical interventions, the RCT of O'Brien et al showed that the surgical arm lowered mean BMI by 12.7 kg/m 2 (95% CI -11.3 to -14.2), relative to a decrease of 1.3 kg/m 2 (95% CI 0.4 to 2.9) in the lifestyle change management arm in this RCT of 50 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Atualmente, aproximadamente 380 milhões de crianças e adolescentes possuem excesso de peso no mundo (GENITSARIDI SM, et al, 2019). Devido ao impacto psicológico e ao estigma produzidos pela obesidade, é essencial que ela seja abordada com sensibilidade pelo profissional de saúde (SELVENDRAN SS, et al, 2018). O emagrecimento é um dos principais objetivos no tratamento desta comorbidade, já que adolescentes obesos possuem maior incidência de hipertensão, infecções respiratórias, apneia obstrutiva do sono, acantose nigricans e maior dificuldade de aprendizagem (GENITSARIDI SM, et al, 2019).…”
Section: Considerações Finaisunclassified
“…regular practice of physical and/or sports exercise has significant health benefits (REINER-HEINRICH et al, 2013;WARBURTON;BREDIN, 2017) However, some of the main health problems found in today's society can be associated with high rates of physical inactivity (OMS, 2010; TROST; BLAIR; KHAN, 2014). The health problems that physical inactivity can cause include overweight, obesity and their resulting diseases such as high blood pressure and skeletal or muscle problems (MONASTA et al, 2010;McCARTHY et al, 2014;SELVENDRAN et al, 2018). Other studies indicate that the practice of physical-sportive exercise tends to gradually decrease as the age advances, particularly in the case of women (DUMITH et al, 2011, MURILLO PARDO et al, 2015.…”
mentioning
confidence: 99%